Multi-scale Optimization of Hybrid Sodium Sulfate-activated Binders - Monin, Chloé (Université d'Ottawa | University of Ottawa, 2024)
Civil engineering plays a crucial role in addressing pressing societal concerns, from ensuring safety to promoting sustainability. With the ongoing challenge of climate change, there is an increasing need to mitigate carbon emissions, which can be achieved by driving innovation in construction materials and methods. Concrete, essential for modern infrastructure, is environmentally impactful mainly due to its dependence on Portland cement in production, andthe large volumes that are being consumed to fulfill societal needs. This thesis investigates hybrid alkali-activated materials (AAMs) as a viable alternative to traditional concrete formulations. By substituting a significant portion of Portland cement with supplementary cementitious materials (SCMs), hybrid AAMs offer a pathway towards reducing environmental footprint while maintaining performance. The focus of this work is on optimizing sodium sulfate-activated hybrid AAMs comprising metakaolin, limestone, and Portland cement, along with an alkali-activator, in this case sodium sulfate. Through a systematic approach using factorial design of experiments (DOE) and multi-scale testing, this research aims to tailor the performance of hybrid AAMs to meet both early-age strength requirements and long-term performance. Initial findings indicate that the addition of sodium sulfate enhances the reactivity of metakaolin, allowing for a reduction in Portland cement content without compromising early-age performance. However, challenges have been identified through this work concerning the long-term strength of hybrid AAMs, which are tentatively attributed to phase instability and higher porosity (as inferred from the decreased electrical resistivity). Recommendations emphasize a nuanced approach to binder composition, balancing alkali content with Portland cement and metakaolin content to ensure optimal strength development. The proposed framework proposes the following steps in designing hybrid AAMs activated with sodium sulfate: (1) Determining binder composition: Identify optimal ratios of metakaolin, limestone, and Portland cement to achieve the desired later age performance and reduce carbon footprint. (2) Achieving sulfate balance: Evaluate the adequate sulfate content to achieve sulfate balancein the system.ii (3) Optimizing alkali content: Evaluate the minimal alkali content needed to achieve the required early-age strength. (4) Re-evaluating binder composition: If the selected alkali content compromises later-age strength, reassess binder composition. Replacing metakaolin by limestone increases the tolerance of the system to high alkali content and increasing Portland cement content may help reduce the amount of alkalis needed.
Keywords: Hybrid alkali-activated materials